Infection with Spiroplasma kunkelii on temperate and tropical x temperate maize in Argentina and development of a tool to evaluate germplasm - Barontini, Javier Miguel; Peña Malavera, Andrea; Ferrer Lanfranchi, Mariana; Torrico Ramallo, Ada Karina; Maurino, Maria Fernanda; Gimenez, Maria De La Paz (Springer, 2021)
Corn stunt disease is a disease that extends from the southern United States to Argentina and is one of the most important diseases in warm subtropical areas of the continent, periodically causing yield reductions in maize. The aims of this study were to develop a severity scale, estimate the effect of corn stunt caused by Spiroplasma kunkelii in maize hybrids, and identify attributes related to yield loss that would be useful to evaluate germplasms. Under artificial inoculation conditions with infective and non-infective insects, symptoms were grouped to develop and validate a scale and a severity index. Disease severity, moment of appearance of the characteristic symptom, pathogen concentration, and effect on yield were correlated for eight temperate and temperate x tropical commercial and precommercial hybrid maize germplasms. We developed and validated a 7-score severity scale. The characteristic symptom of S. kunkelii infection occurs earlier in the temperate germplasm than in the tropical x temperate germplasm. The performance of two of the four temperate germplasms was remarkable compared to the hybrids. Severity and pathogen concentration were correlated with each other, and both correlated with yield and with yield reduction. The moment of appearance of the characteristic disease symptom did not correlate with the other attributes. The severity index and the pathogen concentration may be useful to evaluate germplasm.